Sally goes to the mountains - Huneck, Stephen (New York : Abrams Books for Young Readers, 2001)
Sally, a black Labrador retriever, is on her way to go camping in the mountains.
Five Owls
School Library Journal
Wilson's Children
1.5
K-3.
K-3
Keywords: Camping -- Juvenile fiction; Dogs -- Juvenile fiction; Camping -- Fiction; Dogs -- Fiction; Camping -- Fiction; Dogs -- Fiction